Tryonia (Pteridaceae) in Brazil - Della, Aline Possamai; Prado, Jefferson [UNESP] (Springer Nature, 2020)
Tryonia is a monophyletic genus of leptosporangiate ferns, composed by four species, which occur mainly in the Brazilian Atlantic Rainforest reaching to Uruguay and in forests and on rock outcrops of the Espinhaço Range. Considering its recent segregation from Eriosorus and Jamesonia, the objective of this work was to carry out the taxonomic study of Tryonia for Brazil, in order to elaborate its monograph in the Flora of Brazil 2020. The present study was based on morphological analyses of material deposited in 25 Brazilian herbaria plus some other collections deposited in foreign herbaria, recent collections made by the authors, and scanning electronic microscopy of the spores. Additionally, a revision of the literature was also carried out. Four species were recognized: T. areniticola, T. myriophylla, T. schwackeana, and T. sellowiana. We provide an identification key for the species, descriptions, illustrations, as well as geographic distribution data, comments, and list of selected specimens examined for each taxon. We also provide a list of exsiccatae containing all studied gatherings.
Keywords: Brazilian Atlantic Rainforest; Eriosorus; Ferns; Flora; Jamesonia; Pteridoideae